Application of fenugreek in ruminant feed: implications for methane emissions and productivity - Xiangbiao Zeng; Yiwen Chen; Wenjuan Li; Shijun Liu (PeerJ, 2024)
Background Human demand for meat and dairy products will increase as a result of economic development and population growth, and the farming of ruminants, such as cattle and sheep, will also increase. Methane (CH4) emission from the enteric fermentation of ruminant livestock is a major source of greenhouse gas emissions and a significant contributor to global warming. Meanwhile, growth performance is often limited and animals are more vulnerable to diseases in high-density, intensive farming, greatly reducing livestock productivity, so developing ways to reduce CH4 emissions and improve ruminant productivity has become a research hotspot. Studies have reported that fenugreek (Trigonella foenum-graecum L.) as feed additives have the potential to reduce ruminant methane and improve the productivity. However, systematic reviews of such studies are lacking. Methodology In this review, databases of Google Scholar, Web of Science, PubMed, Scopus and Science Direct were used for the literature search. The initial keywords search was fenugreek or Trigonella foenum-graecum L. For more focused search, we added terms such as methane, rumen fermentation, growth, milk production and antioxidants. All were done for ruminants. The literature that conforms to the theme of this article is selected, summarized, and finally completed this article. Results By regulating the rumen microbiome (suppressing protozoans, methanogenic bacteria, and fungi), fenugreek can lower CH4 emissions according to many in vitro anaerobic fermentation experiments. Fenugreek secondary metabolites (saponins and tannins) are responsible for this impact, but it is still unclear exactly how they work. Therefore, more long-term in vivo experiments are needed to verify its efficacy. Fenugreek is also rich in alkaloids, amino acids, flavonoids, saponins and phenolic acids. These compounds have been shown to have beneficial effects on ruminant growth, lactation, and total antioxidant capacity. Therefore, fenugreek has a great opportunity to develop into a new green feed additive. Conclusions This review provides a summary of the effect of fenugreek and its bioactive compounds on rumen fermentation, CH4 emissions and production performance by ruminants. In addition, based on the available data, the possible biochemical pathway of fenugreek to reduce CH4 emissions in ruminants was described. Overall, the livestock feed industry has the opportunity to develop natural, environmentally-friendly feed additives based on fenugreek.